The effects of Facebook advertisements on the working adult's purchasing behavior - Sasitharan, Githa Devi; Hasan, Hamisah; Bolong, Jusang; Osman, Mohd Nizam (Universiti Putra Malaysia Press, 2016)
Effectiveness of advertising on Facebook has been a constant debate among scholars with contradicting opinions. Subsequently, this study aims to explore the effectiveness of Facebook advertisements in driving awareness and sales conversions among the consumers. By using Hierarchy of effects theory framework, this study further analyzed on the factors that influence consumer’s purchasing behavior through Facebook advertisements. Among the factors examined in this study were, consumer’s awareness towards advertisements placed at home page, profile page, fan page and group page that they are member of. Besides, characteristics of Facebook advertisements such as format; color; interactivity; reliability and relevancy of Facebook advertisements in affecting consumer’s purchasing behavior were also studied. A quantitative research method was utilized by using a survey method. Systematic sampling method was used on 415 respondents, who were the working adults in Klang Valley. Data was collected using survey questionnaire. The findings of this study revealed that, though consumers were aware of Facebook advertisements placed on their Newsfeed wall, however they do not click on the advertisements or proceed with purchases due to the security and privacy reasons. Therefore, this study further concludes that, by having a group pages that are targeted besides ensuring the relevancy of the Facebook advertisement to the target audience, advertisers could increase users’ preference towards advertised products or services and subsequently influence their purchasing decisions.